The Role of the Family in Children's Emotional Social Development - Hafizah Delyana; Mudjiran Mudjiran (Universitas Negeri Padang, 2020)
Social emotional development of children is the development of behavior in children where children are asked to adjust to the rules that apply in the community. Thus, social-emotional development is one aspect of development that is very important for every child because this is one of the determining factors for their success in the future. This can be realized through the process of forming good social and spiritual emotions so that children will be able to develop their potential to the maximum. Thus, families need to pay attention to the process of child development so that it runs optimally. This research is a literature study. The purpose of this study is to explain; 1) the theory of social emotional development, 2) the factors that influence children's social emotional development, 3) the role of the family in the social emotional development of children, and 4) learning activities to optimize the social emotional development of children. The explanation of the four points discussed above will greatly assist parents and teachers in understanding and improving children's social emotional abilities.